2009
DOI: 10.1088/0957-4484/20/41/415603
|View full text |Cite
|
Sign up to set email alerts
|

Block copolymer mediated stabilization of sub-5 nm superparamagnetic nickel nanoparticles in an aqueous medium

Abstract: The paper presents a facile method for decreasing the size of water dispersible Ni nanoparticles from 30 nm to 3 nm by the incorporation of a passivating surfactant combination of pluronic triblock copolymer and oleic acid into a wet chemical reduction synthesis. A detailed study revealed that the size of the Ni nanoparticles is critically governed not only by the concentration of the tri block copolymers but also dependent on the hydrophobic nature of the micelle-core formed. The synthesized Ni nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 63 publications
3
30
0
Order By: Relevance
“…For the fabrication of Ni nanoparticles, methods such as sputtering [ 13 , 14 ], solution glow discharge [ 15 ], pulsed laser ablation [ 6 ], reversed micelles [ 16 ], thermal decomposition [ 17 - 20 ], and wet chemical reduction [ 7 , 21 , 22 ] are used. Among them, the ones based on thermal decomposition are preferred.…”
Section: Introductionmentioning
confidence: 99%
“…For the fabrication of Ni nanoparticles, methods such as sputtering [ 13 , 14 ], solution glow discharge [ 15 ], pulsed laser ablation [ 6 ], reversed micelles [ 16 ], thermal decomposition [ 17 - 20 ], and wet chemical reduction [ 7 , 21 , 22 ] are used. Among them, the ones based on thermal decomposition are preferred.…”
Section: Introductionmentioning
confidence: 99%
“…He et al used the Stable Ni nanoparticles of 24-200 nm in size pre-pared by a thermal decomposition method and their result showed that with the increase of particle size, the saturation magnetization increases monotonically, and the coercivity decreases at first and then increases. These results provided evidence for the existence of size effect and shape anisotropy in Ni nanoparticles [40,[41][42][43].…”
Section: Pharmacokinetics Of Magnetic Nanoparti-cles 21 Absorption mentioning
confidence: 82%
“…This anomalous enhancement of the effective anisotropy indicates that the maximum in the ZFC magnetization does not correspond to the typical blocking temperature of the noninteracting particles, where inter-particle interaction, including dipole–dipole and exchange, plays a significant role in the temperature dependence of the magnetization. An enhancement of the effective magneto-crystalline nanoscale anisotropy is also observed, such as K eff = 1.46 × 10 6 erg/cm 3 in < d > = 11 nm and K eff = 7.03 × 10 6 erg/cm 3 in < d > = 3.71 nm, for Ni nanoparticles fabricated by the chemical reduction synthesis method [ 27 ]. Similar behaviors are also observed in Co nanoparticles [ 28 ].…”
Section: Resultsmentioning
confidence: 99%